Keluarga sebagai pilar utama dalam pembentukan nilai sosial anak - Nur Amalya, Rizqi; Khasanah, Nur (Jurnal Pendidikan Agama Islam, 2025)
The family is the first and most important social environment in shaping a child's character. From birth, children are influenced by the values ​​and culture within their family, such as empathy, discipline, morality, and responsibility. The formation of these values ​​occurs through socialization, parenting, and parental example. This study aims to analyze the role of the family as the primary foundation in shaping children's social values ​​by examining previous research. The method used was a literature review, examining relevant scientific literature. The results indicate that democratic parenting and effective communication are the best strategies for developing positive social behavior in children. However, the challenges of the digital era are factors that families need to consider in maintaining the quality of interactions and the formation of children's social values. Collaboration between families, schools, and the community is necessary for the consistent and ongoing development of children's social character.